Generalized diffusion theory of hydrodynamical particle migration in suspensions. Part 1: The case of equal densities - Diep, Nguyen Van (Vietnam Journal of Mechanics, 1997)
The general continuum theory has been developed for two-phase flows of fluid with deformable particles, where the micro-deformation of particles and the relative motion between phases have been taken into account [1-3]. This paper is concerned with using the simplest model from developed general theory for modeling of particle migration in suspensions- one of the most important and complicated aspects of particle-liquid two-phase flows, that has been observed and studied by many authors. For this purpose it is considered the motion of Newtonian fluid-rotating rigid spherical particles two-phase continuum with specialized nonlinear constitutive equations, when the particle and fluid have equal densities. The obtained equation system has been used for studying quantitatively particle migration problem in the circular Couette flow.